2006
DOI: 10.1007/s11199-006-9048-5
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sex Friendships: Who has More?

Abstract: This is the first study to examine the independent, simultaneous, and relative roles of several factorssex, relationship commitment, perceptions of the benefits vs. costs of cross-sex (vs. same-sex) friendships, gender role orientation, and sexism-in the number of cross-sex (vs. same-sex) friendships people have. The latter four constructs were independently found to predict participants' proportions of cross-sex friendships. Furthermore, a model comprised of all five factors provided a very good fit to the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…One of the first author's previous studies (Lenton & Webber, 2006) provided a second source. In that study, 40 role-words assessed participants' gender diagnosticity, Lippa and Connelly's (1990) reformulation of gender role orientation.…”
Section: Methodsmentioning
confidence: 99%
“…One of the first author's previous studies (Lenton & Webber, 2006) provided a second source. In that study, 40 role-words assessed participants' gender diagnosticity, Lippa and Connelly's (1990) reformulation of gender role orientation.…”
Section: Methodsmentioning
confidence: 99%
“…First, both men and women may be perceived as being more willing to help coworkers of the same sex than they are coworkers of the opposite sex (perhaps a sense of "having each others' backs" due to their shared sex). Previous research suggesting that men and women tend to have more friendships with individuals of the same sex as opposed to those of the opposite sex (Lenton & Webber, 2006, Reeder, 2003, Werking, 1997, in addition to even preferring these friendships (Rose, 1985), lends support to this explanation.…”
Section: Sex Composition Of the Relationship Organizational Members mentioning
confidence: 87%
“…! individuals who reported that they preferred cross-sex friendships reported that those friendships were higher in closeness, trust, caring, having common interests, and providing narcissistic benefits than those respondents who reported having a preference for same-sex friends. Further, relationship commitment, perceptions of the benefits, gender role orientation, and sexism were independently found to predict participants' proportions of cross-sex friendships (Lenton & Webber, 2006). Specifically, for individuals low in romantic relationship commitment, increasing commitment was associated with having more cross-sex friendships, but for individuals high in romantic relational commitment, increasing commitment was associated with having fewer cross-sex friendships.…”
Section: Male-female Workplace Friendshipsmentioning
confidence: 90%
See 1 more Smart Citation
“…Connecting communication across work and personal spheres, I also draw from previous research demonstrating that individuals' close interpersonal relationships may influence both sexist attitudes and workplace behaviors (e.g., Lenton & Webber, 2006;Helms, Walls, Crouter, & McHale, 2010;Kapoor, Pfost, House, & Pierson, 2010;Brands & Kilduff, 2014;Kim & Dew, 2016;Carnes, 2017;Huffman, Matthews, & Irving, 2017;Umukoro & Oboh, 2017;Xie, Shi, & Ma, 2017;Yucel, 2017;Pepli, Godlewska-Werner, Po, & Lewandowska-Walter, 2018). I assume that this effect will persist in terms of intolerance for and reporting of harassing behaviors at work.…”
Section: Introductionmentioning
confidence: 99%